Application of Menu Ordering Information System Design at Kawas Truck Café with WEB Design - Rahdian Kusuma Atmaja; Hari Sugiarto; Priyono Priyono; Sugiono Sugiono; Ade Setiawan (Institute of Computer Science (IOCS), 2022)
Kawas Truck Cafe is a business entity engaged in the culinary field. The cafe does not yet have an information system that can assist in various processes in it, such as the ordering process, and sales transactions and reports. This can cause problems such as human error in the ordering process. The use of stationery and paper when recording menu orders results in overlapping orders, unordered delivery of orders. The report process at this cafe still uses conventional methods in recording and storing order transaction data. So to overcome these problems, the author makes a computerized system for ordering menus at the Kawas Truck cafe to be more efficient. In making this web, the author uses programming languages ??such as PHP, HTML, javascript, css, jquery with several features such as login, menu data, customer data, user data, sales transactions, orders, and reports that can be accessed by company owners and cashiers. By creating a computerized system, the author can help the ordering process, sales to reporting at Kawas Truck Cafe, to achieve effective business activities and time efficiency in company activities.